Implementation of Creating Start up Used Waste of Agroindustry Company - Hamdani, Anwar; Fatonah, Siti; Gusti Putu Diva Awatara, I (International Journal of Engineering and Technology, 2018)
This study aims to create new entrepreneurs by utilizing agroindustry waste companies so as to create business opportunities for communities around the agroindustry company's location and improve the company's rating in environmental management and protection (PROPER) with corporate social responsibility and community empowerment program.This research was conducted survey on agroindustry company in Indonesia. The sample in this study was conducted 40 respondents involved in the utilization of waste into added value company. Data collection methods are interview, observation, documentation, questionnaire and focus group discussion. Analysis technique used is spider net analysis.The results of this study indicate that creating new entrepreneurs can be done by utilizing waste agroindustry companies so as to provide employment opportunities and reduce unemployment, while agroindustry companies can benefit in the form of improved performance ratings in the protection and environmental management (Proper) so that a positive impact on reputation companies, ease of access to credit and sustainability of the company in the future.
Keywords: startup; waste; CSR; beyond compliance; entrepreneur; agroindustry.